Job Satisfaction, Leadership Styles, Demographic Variables and Organisational Commitment among Pharmacists in Vietnam - Dung, Luu Tien; Ho, Dinh Phi; Hiep, Nguyen Thi Kim; Hoi, Phan Thi; Hanh, Duong Thi Phuong (The South East Asian Journal of Management, 2019)
Research Aims: To analyse the organisational commitment of pharmacists in Vietnamese enterprises, incorporating elements such as job satisfaction, leadership style and demographic variables. Design/Methodology/Approach: Based on a primary data sample, collected from 300 pharmacists in professional organisations (universities, hospitals, pharmaceutical companies and drugstore chains), and a structural equation model (SEM). Research Findings: The results show that organisational commitment is significantly dependent on perceived job satisfaction, leadership styles and demographic variables by pharmacists. Predictors of pharmacists' organisational commitment differed significantly. Theoretical Contribution/Originality: This is the first study to consider factors affecting organisational commitment among pharmacists in Vietnamese enterprises. Managerial Implications in the Southeast Asian Context: This study could have potential practical implications in pharmacy management. Human resource management systems in each type of organisation (universities, hospitals, pharmaceutical companies and drugstore chains) must be aware of different predictors that affect the pharmacists' commitment to their respective organisations and devise appropriate managerial standards. Research Limitations and Implications: Earlier research has shown that some control variables, such as age, gender, marital status, number of years in an organisation and level of education, which influence organisational commitments in particular, were not included in the model as direct control variables. Further research should use these control variables in their models to obtain a more complete explanation of organisational commitment among pharmacists in Vietnam.